RARE LETHAL MIDLINE GRANULOMA OF THE NASOPHARYNX STEWARD'S GRANULOMA) - Ghani, Rehman; Nabi, Ghulam; Akhtar, M. (Journal of Ayub Medical College Abbottabad, 1992)
ABSTRACT: We report a case of lethal midline Granuloma of the Nasopharynx. Lethal midline Granuloma of the nose is a rare tumor and its occurrence in the Nasopharynx is still more rare.